Long-Term Health Effects of Vietnam-Era Military Service: A Quasi-Experiment Using Australian Conscription Lotteries - David W. Johnston; Michael A. Shields; Peter Siminski (Institute for the Study of Labor (IZA), 2015)
This paper estimates the long-term health effects of Vietnam-Era military service using Australia's National conscription lotteries for identification. Our primary contribution is the quality and breadth of our health outcomes. We use several administrative sources, containing a near-universe of records on mortality (1994-2011), cancer diagnoses (1982-2008), and emergency hospital presentations (2005-2010). We also analyse a range of self-reported morbidity indicators (2006-2009). We find no significant long-term effects on mortality, cancer or emergency hospital visits. In contrast, we find significant detrimental effects on a number of morbidity measures. Hearing and mental health appear to be particularly affected.
Keywords: H56; I10; I13; 330; military service; health; conscription; Australia; Vietnam War